2015
DOI: 10.1002/bmc.3606
|View full text |Cite
|
Sign up to set email alerts
|

Qualification and application of a liquid chromatography–quadrupole time‐of‐flight mass spectrometric method for the determination of trastuzumab in rat plasma

Abstract: An liquid chromatography-quadrupole time-of-flight (QqTOF) mass spectrometric method was developed for the determination of humanized or human monoclonal antibodies in rat plasma at the early drug discovery stage. Trastuzumab was used as a model monoclonal antibody. The method consisted of immunoprecipitation followed by tryptic digestion for sample preparation and LC-TOF-MS/MS analysis of specific signature peptides in the positive ion mode using electrospray ionization for analysis. A stable isotope-labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The calibration curves had quadratic regressions for all antibodies over the studied concentration range with correlation coefficients r > 0.990 and an LLOQ of 1 μg/mL was easily achieved by this method. The sensitivity was generally enough for most preclinical PK studies to cover the expected concentration range throughout a PK time course to calculate PK parameters for antibody drugs . Using a larger volume (≥40 μL) in the sample preparation method, more optimized conditions of LC/TOF‐MS/MS or a more sensitive instrument (e.g.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The calibration curves had quadratic regressions for all antibodies over the studied concentration range with correlation coefficients r > 0.990 and an LLOQ of 1 μg/mL was easily achieved by this method. The sensitivity was generally enough for most preclinical PK studies to cover the expected concentration range throughout a PK time course to calculate PK parameters for antibody drugs . Using a larger volume (≥40 μL) in the sample preparation method, more optimized conditions of LC/TOF‐MS/MS or a more sensitive instrument (e.g.…”
Section: Resultsmentioning
confidence: 96%
“…The previous method was modified to incorporate on‐bead digestion to quantify many antibodies. Each 24‐μL aliquot of plasma study samples, QCs and STDs was separately mixed with 370 μL of PBS containing 0.1% Tween 20 and 30 μL of magnetic bead suspension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent comparative studies, Peng et al developed and validated a simple, sensitive, specific and precise LC-MS/MS assay for quantitation of infliximab PK in human serum by using isotopelabeled signature peptide as the internal standard (IS), which achieved an excellent correlation with ELISA detection [73]. ParK et al applied LC-MS/MS quadruple time-of-flight mass spectrometric method (QTOF) for the determination of trastuzumab in rat plasma with good sensitivity (LLOD 0.5 µg/ml) and results in consistence with ELISA assay (R 2 =0.9104) [74]. Zhang et al reported a generic automated LC-MS/MS method for the pharmacokinetic study of a mAb in cynomolgus monkey with comparable data by the immunoassay data as well [75].…”
Section: Lc-ms/ms and Bla Bioanalysis Of Mabsmentioning
confidence: 99%
“…Although for the trastuzumab deamidation monitoring a peptide marker included in the CDR is used, the signature peptide proposed for trastuzumab quantification in the same work is located in the Fab heavy chain region outside the CDR. In addition, the development of a generic method for quantifying mAbs in animal plasma by LC/TOF‐MS/MS has been reported . However, since the specific signature peptides chosen for trastuzumab determination in rat plasma are located within the Fc and are also present in human immunoglobulins, this methodology is not amenable to the quantification of trastuzumab in human plasma and/or serum.…”
mentioning
confidence: 99%